Upper Extremity Deep Vein Thromboses: The Bowler and the Barista - Seth Stake; Anne L. du Breuil; Jeremy Close (Case Reports in Vascular Medicine)
Effort thrombosis of the upper extremity refers to a deep venous thrombosis of the upper extremity resulting from repetitive activity of the upper limb. Most cases of effort thrombosis occur in young elite athletes with strenuous upper extremity activity. This article reports two cases who both developed upper extremity deep vein thromboses, the first being a 67-year-old bowler and the second a 25-year-old barista, and illustrates that effort thrombosis should be included in the differential diagnosis in any patient with symptoms concerning DVT associated with repetitive activity. A literature review explores the recommended therapies for upper extremity deep vein thromboses.